PEMBELAJARAN SEJARAH HUMANISTIK UNTUK MEMPERKUAT PEMAHAMAN SOSIAL DAN KESADARAN KEWARGANEGARAAN - Siti Wuryan, Indah; Djono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
History learning in the twenty-first century is expected not only to develop students’ factual knowledge but also to strengthen their social understanding and citizenship awareness. However, many studies indicate that history instruction is still dominated by memorization-oriented and teacher-centered approaches, limiting students’ opportunities to develop reflection, empathy, and meaningful interpretations of human experiences in the past. This study aims to analyze and synthesize the relationship among humanistic history learning, historical empathy, social understanding, and citizenship awareness. The study employed a literature review method using national and international journal articles obtained from academic databases. Data were analyzed through thematic identification, categorization of findings, comparison of research results, and conceptual synthesis of relevant literature. The findings reveal that humanistic history learning creates meaningful, reflective, and student-centered learning experiences. This approach contributes to the development of historical empathy, enabling students to understand the perspectives and experiences of people in the past. Historical empathy subsequently strengthens social understanding of diversity, conflict, and social dynamics, which ultimately supports the development of democratic, critical, and responsible citizenship awareness. This review offers a conceptual synthesis linking humanistic learning, historical empathy, social understanding, and citizenship awareness into an integrated framework for history education development.